The prediction of the interaction between shipboard antennas and their environment - Botha, Louis (My University, 2016)
This dissertation discusses the interaction between shipboard antennas and their environment. The emphasis is on the Use of the Method of Moments to calculate the currents on the structure of the ship. These currents are induced by the antennas mounted on the structure of the ship. The parameters (such as grid spacing and wire radius) to use in creating a wire grid model of the ship is investigated and recommended values given. A sample ship is analyzed and the results obtained compared with measurements done in an unechoic chamber.
A dissertation submitted to the faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of science in Engineering Johannesburg 1991
Keywords: Antennas (Electronics)--Research--South Africa; Moments method (Statistics)--Research